THE EFFECTIVENESS OF USING SCRABBLE AND BINGO GAME TECHNIQUE TOWARD STUDENTS’ VOCABULARY MASTERY AT THE TENTH GRADE OF SMA N 2 METRO ACADEMIC YEAR 2013/2014 - Ahmad Rosidi; Eva Faliyanti (UNIVERSITAS MUHAMMADIYAH METRO (MUHAMMADIYAH UNIVERSITY OF METRO), 2014)
Abstract: Vocabulary mastery is the activity to enrich the vocabulary, they master the vocabulary in order to be able to master four language skills. The problem formulation of this research are; (1) Is there any difference influence of using Scrabble and Bingo Game Technique toward Students’ Vocabulary Mastery at The Tenth Grade of SMA N 2 Metro Academic Year 2013/3014? (2) Which one is more effective between Scrabble and Bingo Game Technique toward Students’ Vocabulary Mastery at The Tenth Grade of SMA N 2 Metro Academic Year 2013/3014 ?, The object of this research are; (1) To know whether there is any difference Influence of using Scrabble and Bingo Game Technique toward Students’ Vocabulary Mastery at The Tenth Grade of SMA N 2 Metro Academic Year 2013/3014, (2) To know which one is more effective between Scrabble and Bingo Game Technique toward Students’ Vocabulary Mastery at The Tenth Grade of SMA N 2 Metro Academic Year 2013/3014. This research is Quantitative research. Research design that will be used in this research is true experimental design (pretest posttest control group design).. The population of this research is the students’ of SMA N 2 Metro Academic Year 2013/2014 that consist of 660 students. The sample is 60 students. As the sample, 30 as experimental class and 30 as control class. In taking sample, the researcher used the cluster stratified random sampling. The data collecting tehniques the researcher used try-out, pre-test, treatment and post-test. The data analyzing tehniques, the researcher used normality test, homogenity test and hypothesis test. The differences of both the tehnique are Scrabble Game can make the students feel enjoy, creative and have a challenge and Bingo Game gives the students opportunity to identify the word interestingly. Based on the data analysis, the researcher uses t-test formula. The researcher got the result of tobserved = 3,69 and ttable is 2.00. it means that tobserved > ttable. And the criterion of ttest is Ha accepted if tobserved > ttable . So, there is any difference Influence of using Scrabble and Bingo Game Technique toward Students’ Vocabulary Mastery at The Tenth Grade of SMA N 2 Metro academic year 2013/2014.